A Study of “The Common Law Tradition: Deciding Appeals” - Arno C. Becht (Washington University Law Quarterly, 1962)
The chief object of this review is to give an accurate idea of the contents of Professor Llewellyn's book, The Common Law Tradition: Deciding Appeals, thus supplying a general background for the other articles. The perfect review, for this purpose, would eliminate all personal reactions of the reviewer, but there are reasons why this ideal is impossible. The mere processes of selection and emphasis require some exercise of discretion, and, moreover, the book provokes responses which will probably show through to others even though they are unconscious. I have tried to compromise with the problem in this way: Part I is devoted to a quite extensive survey of the book, and in this I have suppressed my reactions as much as I could, (not entirely) and have let the author speak for himself a good deal of the time. In Part II I have tried to convey some impression of the book as a whole, an operation that obviously requires more subjective methods, and Part III is a collection of frankly personal comments which are offered for what they are worth and which may also serve to discount the less overt evaluations that have affected the rest of the review.
Keywords: Karl Llewellyn